Nilai Dan Karakter Dalam Filsafat Dan Ilmu Pengetahuan - Fajar, Muhammad; Nurikhsan, Muh; Alwi, Khairunnisa; Alfiah JS, Nur; Najamuddin, Najamuddin; Agus, Andi Aco (Jurnal Tugas Akhir Mahasiswa Pendidikan Sosiologi, 2026)
The purpose of this study is to describe the values in philosophy and science, national character in philosophy, and the integration of national values and character in science. This study is a qualitative study with a descriptive approach. Data collection technique is in the form of library research. Data is obtained through books or journals related to values and character in philosophy and science. The results of the study show that values in philosophy are studied through one of the branches of philosophy, namely axiology. Values in knowledge are a guide to seeing the importance of a fact. The philosophy of science plays a role in the formation of national character through self-understanding and social life, and religious values in order to realize a critical, wise, and cultured nation. Integration of values and characters that reflect the nation's identity must be carried out in the learning process from planning to evaluation so that students with character and morals can be formed.